Role of the forkhead protein FoxO1 in β cell compensation to insulin resistance - Okamoto, Haruka (American Society for Clinical Investigation, 2006)
Diabetes is associated with defective β cell function and altered β cell mass. The mechanisms regulating β cell mass and its adaptation to insulin resistance are unknown. It is unclear whether compensatory β cell hyperplasia is achieved via proliferation of existing β cells or neogenesis from progenitor cells embedded in duct epithelia. We have used transgenic mice expressing a mutant form of the forkhead-O1 transcription factor (FoxO1) in both pancreatic ductal and endocrine β cells to assess the contribution of these 2 compartments to islet expansion. We show that the mutant FoxO1 transgene prevents β cell replication in 2 models of β cell hyperplasia, 1 due to peripheral insulin resistance (Insulin receptor transgenic knockouts) and 1 due to ectopic local expression of IGF2 (Elastase-IGF2 transgenics), without affecting insulin secretion. In contrast, we failed to detect a specific effect of the FoxO1 transgene on the number of periductal β cells. We propose that β cell compensation to insulin resistance is a proliferative response of existing β cells to growth factor signaling and requires FoxO1 nuclear exclusion.